THE COMPARATIVE ANALYSIS OF EMPLOYEE PERFORMANCE BEFORE AND AFTER TRAINING AT BANK INDONESIA IN MANADO - Paat, Gracia Natalia Gloria; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Training is a systematic process, which helps people to learn how to be more effective at work by modifying knowledge, skills or attitudes through learning experience to achieve effective performance. The object of case study from this research is Bank Indonesia in Manado. Research objective is to analyse the differences in employee performance before and after training. Variables which have been used in this research are: quality/ quantity of work, planning/ organizing, initiative/ commitment, teamwork/ cooperation and communication. This study applies with comparative method using paired sample t-test to verify and to prove the research hypothesis. The numbers of respondent are 40 employees who already follow the training. The result shows that quality/ quantity of work, planning/ organizing, initiative/ commitment, teamwork/ cooperation and communication giving a significant difference in employee performance before and after training at Bank Indonesia in Manado. The training program is one of the valuable systems as a way to improve employee performance. Therefore, management of Bank Indonesia also needs to increase the effectiveness of training and enhance the variety of the material and module that would be given in the training program. Keywords: training, employee performance